2016
DOI: 10.1371/journal.pone.0146425
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of Older Men in Seven European Countries: A Multilevel Approach in the Framework of an Ecological Model

Abstract: BackgroundSeveral studies on elder abuse indicate that a large number of victims are women, but others report that men in later life are also significantly abused, especially when they show symptoms of disability and poor health, and require help for their daily activities as a result. This study focused on the prevalence of different types of abuse experienced by men and on a comparison of male victims and non-victims concerning demographic/socio-economic characteristics, lifestyle/health variables, social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 90 publications
(113 reference statements)
3
44
0
3
Order By: Relevance
“…This result is consistent with other studies, such as one carried out in seven European countries, that identified male as under-recognized and under-reported, due to traditional and sexist social and cultural norms abuse that prevent older men for reporting abuse. The authors emphasize that increased age, financial strain and greater social support seemed linked with a decreased probability of being abused (10) . According to Lachs and Pillemer (11) , an aggressor and an older adult sharing the living environment is a major risk factor for abuse.…”
Section: Discussionmentioning
confidence: 93%
“…This result is consistent with other studies, such as one carried out in seven European countries, that identified male as under-recognized and under-reported, due to traditional and sexist social and cultural norms abuse that prevent older men for reporting abuse. The authors emphasize that increased age, financial strain and greater social support seemed linked with a decreased probability of being abused (10) . According to Lachs and Pillemer (11) , an aggressor and an older adult sharing the living environment is a major risk factor for abuse.…”
Section: Discussionmentioning
confidence: 93%
“…It is also possible that exposure to violence increases the awareness of somatic symptoms [34]. Other authors have shown a significant association between experiencing childhood and adolescent emotional and sexual abuse and severity of somatic symptoms [15], and have also reported that, for older men, the probability of being abused increases along with the increase of somatic and anxiety symptoms [35]. In particular, psychological abuse emerged as related to somatic symptoms; however, also other factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on elder abuse among older Chinese people have yielded comparable prevalence rates (20.0‐26.8% for psychological and 2.4‐2.5% for physical abuse) next to those returned by their counterparts focusing on Europeans using similar methodologies (10.4‐29.7% for psychological and 1.0‐4.0% for physical abuse) . Older Chinese people with cognitive and/or physical impairment are particularly prone to abuse, likely a result of victims being perpetually subjected to revictimization and chronic stress in abusive relationships due to inability to care for self‐reliance and overreliance on caregiver support .…”
Section: Introductionmentioning
confidence: 99%